Should renal resistive index be considered as a routine predictor in newly diagnosed acute hydronephrosis in patients with unilateral renal colic? - Hamid Dahmarde; Faramarz Fazeli (Medičnì Perspektivi, 2022)
Urinary tract stones are the most common causes of urinary tract obstruction, leading to patient hospitalization in the emergency room. This study is aimed to evaluate the use of the mean resistance index (mRI) to predict hydronephrosis in patients admitted for acute renal colic. This prospective study was performed on 100 patients who were admitted to the emergency department (ED) with unilateral renal colic (RC) problem. At the first visit, the following was done for all patients: 1. blood was taken from them for laboratory studies; 2. ECG and cardiological test; 3. plain film of the urinary tract; 4. аbdominal US; 5. bilateral color doppler ultrasound (CDUS) with renal RI measurement. Based on the information collected at different times during the experiment, patients were divided into two groups: the group that showed signs of dilatation (group A) and the group with hydronephrosis (group B). The obtained data were analyzed statistically by SPSS version 20. A mRI with a 0.68 cut off value was the most accurate (AUC:0.878), and Sensitive (90%) cut-off value for prediction of  hydronephrosis development among patients presenting with RC and renal stone. This cut-off value also provided the highest positive (94%) and negative (76%) predictive values. CDUS with RI measurement is an easy and non-invasive method that provides useful information about urinary tract obstruction stones in patients with unilateral RC. In our study, this method was able to predict successfully the onset of acute renal dilatation. This was done with different levels of sensitivity, specificity, accuracy and diagnostic efficiency that were higher than ultrasound. Daily use of CDUS in ED can improve ultrasound, especially when other methods are contraindicated. For example, the methods by which the patient is exposed to radiation (pregnancy, allergies, renal failure, etc.) or intravenous injection of contrast agents (urography and CT).